Optimalisasi Kelas Ibu Hamil Sebagai Upaya Peningkatan Pengetahuan Ibu Hamil Dan Keluarga Di Wilayah Kerja Puskesmas Sungai Turak - Nurlaila Hayati; Meldawati Meldawati; Siti Noor Hasanah (Universitas Maritim AMNI Semarang, 2024)
Pregnant women's class activities aim to increase knowledge, change mothers' attitudes and behavior so that they understand about pregnancy checks, childbirth, postpartum and newborn care for optimal growth and development. The class for pregnant women coordinated by the Sungai Turak village health center was felt to be less than optimal, where the level of attendance and motivation of mothers in attending the class for pregnant women was felt to be lacking. In January 2024, community service was carried out, in the form of optimizing classes for pregnant women as an effort to increase knowledge of pregnant women and families in the working area of the Sungai Turak Community Health Center. Health cadres should approach pregnant women in their area, to discuss when they can take part in pregnant women's class activities, to then coordinate with the facilitator team. The effort made was to create educational posters about the benefits of attending classes for pregnant women. It is hoped that with attractive posters, pregnant women's interest in taking part in classes for pregnant women will increase. Coinciding with the class schedule for pregnant women, more intensive outreach was carried out, accompanied by posters displayed at the Community Health Center and Posyandu. Thanks to these efforts, the number of pregnant women who attended increased to 24 pregnant women.